2013
DOI: 10.1590/s1516-05722013000400015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of the essential oil from the leaves and flowers of Aloysia gratissima

Abstract: Volatile oils from leaves and flowers of Aloysia gratissima were investigated for their chemical composition and antimicrobial activity against the bacteria Bacilus subtilis, Staphylococcus aureus, Salmonella choleraesuis, Pseudomonas aeruginosa, Streptococcus pneumoniae and the Candida albicans yeast. The minimum inhibitory concentrations (MIC) of the oils were determined by the micro-dilution method, while the chemical composition was determined by GC-MS (gas chromatography mass spectrometry). The fresh leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
(14 reference statements)
2
13
0
3
Order By: Relevance
“…Additionally, trans-caryophyllene and its oxide (7% total) were also identified in the oil composition. A similar sesquiterpene constitution in the oil of A. gratissima leaves and flowers was recently described (Santos et al 2013), although a distinct monoterpene composition was characterized. Other studies identified similar compounds as well as different proportions of guaiol in A. gratissima leaf oil such as 2·6% (Santos et al 2013), 11·5% (Santos et al 2015) and 12·5% of guaiol (Trovati et al 2009).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Additionally, trans-caryophyllene and its oxide (7% total) were also identified in the oil composition. A similar sesquiterpene constitution in the oil of A. gratissima leaves and flowers was recently described (Santos et al 2013), although a distinct monoterpene composition was characterized. Other studies identified similar compounds as well as different proportions of guaiol in A. gratissima leaf oil such as 2·6% (Santos et al 2013), 11·5% (Santos et al 2015) and 12·5% of guaiol (Trovati et al 2009).…”
Section: Discussionsupporting
confidence: 64%
“…A similar sesquiterpene constitution in the oil of A. gratissima leaves and flowers was recently described (Santos et al 2013), although a distinct monoterpene composition was characterized. Other studies identified similar compounds as well as different proportions of guaiol in A. gratissima leaf oil such as 2·6% (Santos et al 2013), 11·5% (Santos et al 2015) and 12·5% of guaiol (Trovati et al 2009). These differences can be attributed to diverse environmental conditions, including the type of soil, climate, plant age and the part of the plant used to obtain the oil (Velasco-Negueruela and Pérez-Alonso, 1993).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations